PENDIDIKAN DALAM BELENGGU KONFLIK: STRATEGI DAN KONDISI PENDIDIKAN DI REPUBLIK YAMAN - Sudarto, Sudarto; Sassi, Komarudin (Lembaga Berugak Baca, 2024)
This research aims to understand the actual condition of the education sector in the Republic of Yemen, along with the strategies that have been prepared in the context of developing and improving the quality of education. The panorama that is being observed is not only a picture of Yemen which until now is still preoccupied by conflicts and political disputes. This paper is expected to be one of the scientific contributions for further research in related fields. The data in this paper was obtained using qualitative research methods by conducting literature studies from various sources. The data collected is presented as it is without providing any interpretation. From these various sources, some data was obtained from official documents. Although with the disclosure of the source of the document, statements or articles that are opinions are minimized so that scientific objectivity is maintained. Based on the studies that have been conducted, an important keyword has been found that covers development in all sectors (including education) in Yemen, namely the Yemen Strategic Vision 2025. Especially in the field of education, the Ministry of Education and Culture has prepared a set of plans and achievement parameters for a certain work period. This article is not proposed as a form of problem solving, but rather is intended as additional literature for a more comprehensive review.